Exogenous feeding in larvae of bilih fish (Mystacoleucus padangensis Blkr) - Kusuma, Hendra; Syandri, Hafrijal; Eriza, Mas (Universitas Malikussaleh, 2025)
The bilih fish (Mystacoleucus padangensis Blkr) is an endemic species in Lake Singkarak, holding significant economic value. However, its population has drastically declined over the past few decades and is currently classified as 'vulnerable'. One of the crucial factors in the successful cultivation of bilih fish is the provision of appropriate feed during the early larval stages, particularly after the depletion of endogenous yolk reserves. This study aims to examine the exogenous feeding phase in bilih fish larvae after the endogenous food supply has been exhausted, which marks the stage when the larvae must begin to rely on external feed for survival and growth. The study employed a Completely Randomized Design of three treatments with four replications each. Treatment A involved feeding Chlorella sp. (days 3-10), followed by Artemia (days 10-20); Treatment B involved Chlorella sp. (days 3-10), followed by artificial feed (days 10-15) and Artemia (days 15-20); and Treatment C involved artificial feed (days 3-10), followed by Artemia (days 10-20). The larvae were reared in tarpaulin tanks with a water volume of 125 L and a stocking density of 2,000±85 individuals, and they were fed to satiation twice a day (morning and evening) for 20 days. Data were analyzed using One-way ANOVA with the IBM SPPS Statistics 25 program. The results showed that the provision of different exogenous feed compositions had no significant effect (PËƒ0.05) on absolute length growth and survival of bilih fish larvae (Mystacoleucus padangensis Blkr). Treatment B produced the best survival (31.75 ± 1.70%) and absolute length growth (3.67 ± 0.21 mm). The results of the water quality parameters show an average temperature of 28±1.2oC, pH 28±1.2, dissolved oxygen 5.6±0.78 mg/l.Keywords: Absolute Length Growth; Bilih Fish Larva; Diet Type; Feed Composition; Survival Rate